Spatial variations in Achilles tendon shear wave speed - DeWall, Ryan J. (2014)
Supersonic shear imaging (SSI) is an ultrasound imaging modality that can provide insight into tissue mechanics by measuring shear wave propagation speed, a property that depends on tissue elasticity. SSI has previously been used to characterize the increase in Achilles tendon shear wave speed that occurs with loading, an effect attributable to the strain-stiffening behavior of the tissue. However, little is known about how shear wave speed varies spatially, which is important, given the anatomical variation that occurs between the calcaneus insertion and the gastrocnemius musculotendon junction. The purpose of this study was to investigate spatial variations in shear wave speed along medial and lateral paths of the Achilles tendon for three different ankle postures: resting ankle angle (R, i.e. neutral), plantarflexed (P; R − 15 deg), and dorsiflexed (D; R + 15 deg). We observed significant spatial and posture variations in tendon shear wave speed in ten healthy young adults. Shear wave speeds in the Achilles free tendon averaged 12 ± 1.2 m/s in a resting position, but decreased to 7.2 ± 1.8 m/s with passive plantarflexion. Distal tendon shear wave speeds often reached the maximum tracking limit (16.3 m/s) of the system when the ankle was in the passively dorsiflexed posture (+15 deg from R). At a fixed posture, shear wave speeds decreased significantly from the free tendon to the gastrocnemius musculotendon junction, with slightly higher speeds measured on the medial side than on the lateral side. Shear wave speeds were only weakly correlated with the thickness and depth of the tendon, suggesting that the distal-to-proximal variations may reflect greater compliance in the aponeurosis relative to the free tendon. The results highlight the importance of considering both limb posture and transducer positioning when using SSI for biomechanical and clinical assessments of the Achilles tendon.